Social portrait of the modern extremist (shahid) (Eurasian Journal of Religious Studies, 2018)
The article examines the phenomenon of shahidism in the context of religious extremism and terrorism. The distortion of this concept by modern ideologists of extremism is shown. The authors emphasize that Islam does not allow violence, and if it is possible, forgiveness, alms, is welcomed. Suicide is categorically forbidden by Islam.Extremists, making a false substitution for the concept of "shahid," sent to certain death hundreds and hundreds of people. The inhuman, cruel essence of destructive religious organizations, in particular ISIL, that use people as a bomb to achieve their narrow-interest interests, is revealed. An analysis of these concepts is given. The problems of occurrence of the phenomenon of shahidism and their eradication in the future are investigated.